HUBUNGAN ANTARA USIA, STATUS GIZI, DAN STATUS IMUNISASI DENGAN KEJADIAN CAMPAK BALITA - Husnul Khotimah (Akademi Kebidanan La Tansa Mashiro, 2013)
The purpose of this study to determine the relationship between age, nutritional status, and status with the incidence of measles immunization in infants in the district of Lebak in 2007-2008. This research uses the analytical method with case-control approach. Population were all infants enrolled in the register book format C1 and toddlers. The sample used was 308, 154 and 154 samples as a case sample as kontrol.Data is secondary data collected retrospectively. Data obtained from C1 as format of the register book case and a toddler at a health center in 2007-2008 Lebak as controls. Data collection tool that checklist sheet. Univariate analysis by descriptive and bivariate analysis using Chi Square test. The results showed that there is a statistically significant relationship between nutritional status and immunization status with the incidence of measles in infants, whereas age was no statistically significant correlation with the incidence of measles in infants.